Residual toxicity of selected organic insecticides to Diaphorina citri (Hemiptera: Liviidae) and non-target effects on Tamarixia radiata (Hymenoptera: Eulophidae) in California. (June 2018) - Tofangsazi, Nastaran; Morales-Rodriguez, Anuar; Daugherty, Matthew P.; Simmons, Gregory S.; Grafton-Cardwell, Elizabeth E.
Abstract: The Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae) threatens California's citrus industry because of its ability to transmit the bacterium, Candidatus Liberibacter asiaticus, associated with huanglongbing (HLB). To reduce the risk of HLB spread, an area-wide management strategy was established to control D. citri in both conventional and organic commercial citrus. In addition, releases of the parasitoid Tamarixia radiata Waterston (Hymenoptera: Eulophidae) as a classical biological control agent have been conducted in certain urban areas of California to improve control of D. citri . The objectives of this study were to document the residual efficacy of organic insecticides against D. citri nymphs, compare the efficacy of multiple applications of the organic spinosad relative to a single application of the non-organic insecticide fenpropathrin, and estimate the non-target effect of selected foliar insecticides on T. radiata . Spinosad + oil showed greater residual control of D. citri nymphs compared to pyrethrins + oil. The effects of organic insecticides were short lived; by 10 d post treatment there was no detectable effect. Fenpropathrin provided significantly longer control of D. citri nymphs and the efficacy of two or more applications of spinosad was comparable to one application of fenpropathrin. Of the organic insecticides, spinosad + oil resulted in the greatest non-target effects on T. radiata and pyrethrins, pyrethrins + oil, and oil alone had the least severe effects on T. radiata . This study provides important information regarding the residual control of D. citri by organic insecticides and their compatibility with the biological control agent T. radiata . Highlights: Spinosad + oil showed greater residuality compared to other organic insecticides. There was no detectable effect of the organic insecticides after 10 days. Two treatments of spinosad provided similar control to one fenpropathrin treatment. Spinosad + oil was as toxic as fenpropathrin to T. radiata nymphs and adults.